Psychopathic Traits Among Serious Juvenile Offenders: developmental Pathways, Multidimensionality, and Stability - Lee, Yeungjeom (Crime & delinquency, 2021)
The link between psychopathy and crime is well-known and a large body of literature has provided empirical support. However, the stability hypothesis of psychopathy has been a critical issue, and there are only a small number of stability studies adopting a developmental perspective. To fill this gap, the current study aims to identify the developmental pathways for the comprehensive psychopathic traits scale and three dimensions across the transition from adolescence to adulthood. The majority of adolescents show stability in their psychopathic traits from adolescent to early adulthood, whereas a small proportion of youth show changes. The findings from this study provide supports for the notion of early identification of young psychopathy. Theoretical and practical implications are discussed.